1988
DOI: 10.1080/03036758.1988.10426471
|View full text |Cite
|
Sign up to set email alerts
|

Cretaceous-Cenozoic lithostratigraphy of the Chatham Islands

Abstract: New mapping on the Chatham Islands, coupled with many new fossil determinations, has significantly refined our understanding of stratigraphic relationships of the Cretaceous-Cenozoic rocks exposed there. The following units are recognisable: Waihere Bay Group (emended), Tupuangi Formation (redefined; 240-400 m; Late Albian-Santonian), Pitt Island Group (emended), Kahuitara Tuff « 225 m; Campanian-Maastrichtian), Southern Volcanics (>300 m; Campanian-Maastrichtian), unnamed Cretaceous sandstone (>0.3 m; Late (?… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(99 citation statements)
references
References 13 publications
5
93
0
1
Order By: Relevance
“…regius 8.42. This prior corresponds to the emergence of the Chatham Islands between 1 and 3 million years ago ( Campbell et al 1994 ;Trewick et al 2007 ;Landis et al 2008 ;Wallis and Trewick 2009 ). We applied Bayesian and maximum likelihood approaches to estimate divergence times at three well-supported nodes.…”
Section: Methodsmentioning
confidence: 99%
“…regius 8.42. This prior corresponds to the emergence of the Chatham Islands between 1 and 3 million years ago ( Campbell et al 1994 ;Trewick et al 2007 ;Landis et al 2008 ;Wallis and Trewick 2009 ). We applied Bayesian and maximum likelihood approaches to estimate divergence times at three well-supported nodes.…”
Section: Methodsmentioning
confidence: 99%
“…The Tupuangi Formation has been recorded only from Pitt Island (Māori: Rangiauria; Moriori: Rangiaotea), the second largest island of the archipelago (Figure 1.2). The unit comprises >400 m of siliciclastic strata deposited in a fluviodeltaic system (Campbell et al, 1993;Mays and Stilwell, 2013) during tectonic extension prior to Cretaceous seafloor spreading between Zealandia and Antarctica (Laird and Bradshaw, 2004). The most complete outcrop succession of this unit occurs at Waihere Bay, on the northwestern portion of Pitt Island, and includes the fossil locality recorded herein (Figure 1.3).…”
Section: Geological Settingmentioning
confidence: 99%
“…The outcrop succession at Waihere Bay is dominated by interbedded carbonaceous siltstone and quartzofeldspathic fine to medium sandstone (Hay et al, 1970;Campbell et al, 1993;Mays and Stilwell, 2013, figure 4). Dozens of these siltstone horizons have yielded compression fossils of macroflora (Mays et al, 2015a(Mays et al, , 2015b(Mays et al, , 2017 and insects (Stilwell et al, 2016).…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…indet), represented by plastron and carapace fragments from the Maungataniwha Sandstone of Hawke's Bay (Wiffen 1981). Marine turtles persisted through the Cenozoic with a possible turtle humérus recorded from the Amuri Limestone (Paleocene) of Marlborough (Fordyce 1979) and possible late Paleocene to early Eocene turtle remains in the Red Bluff Tuff of the Chatham Islands (Campbell et al 1988); the lattermost specimen has been re-identified as a probable sponge (E. Fordyce pers. comm.…”
Section: Introductionmentioning
confidence: 99%